The Multifunctional Role of the Conjunctions Որ, Թե in Eastern Armenian - Abajyan, Anna (Bulletin of Yerevan University B: Philology, 2022)
Thus, to sum up, we can state that Modern Armenian conjunctions որ, թե have a unique place in Eastern Armenianwith theirfrequency of usage, their abilityto form other parts of speech, to express various relationships, to determine the part-of-speech belonging of the words demonstrating conversion in the given sentence, with the ability and flexibility to distinguish an intra-speech type, to show intersemantic nuancesand the uniqueness to express speech stylization. We can state with confidence that the increase in the number of conjunctions in Modern Armenian is primarily due to the composition of conjunctions which are very important in terms of providing wide opportunities for stylistic applications. In this process, the influence of everyday colloquial language, dialects, foreign languages and translated literature is especially huge.